A little history of the world - Gombrich, Ernst Hans Josef (Ernst Hans) 1909-2001.; Mustill, Caroline (New Haven Yale University Press, 2011)
Presents a brief, narrative history of the world, from the Stone Age up to the end of World War II.
Originally published in 2005. With added illustration.
"Originally published under the title Weltgeschichte von der Urzeit bis zur Gegenwart by Steyrermuhl-Verlag, Vienna in 1936" -- Title page verso.
"Published in Germany as Eine kurze Weltgeschichte fur junge Leser by Ernst H. Gombrich.
"1985 by DuMont und Kunst Verlag GmbH und Co. KG, Cologne, Germany." -- Title page verso.
Includes index.
Keywords: World history -- Juvenile literature